Olbert's Balloon Dilatation as a Minimally Invasive Possibility of Treating Ureteral Stricture After Complicated URS-L in Children - Adam Halinski; Adam Halinski; Adam Halinski; Andrzej Halinski; Paweł Halinski (Frontiers Media S.A., 2022)
Olbert's balloon dilatation is a surgical technique used for the treatment of ureteral stricture. Although it is more frequently used in adults, due to the advancing miniaturization of the equipment, this technique has become possible in children. We would like to present five cases of Olbert's balloon dilatation carried out in children with ureteral stricture, aged 12-17 years. All of these children were diagnosed for at least 6 months. Ureteral stricture has been noticed in those patients with a time of a stone residence in the ureter longer than 6 months. The duration of the stone in the ureter varied from 6 to 18 months. The symptoms were abdominal pain, renal colic pain, UTI, fever, vomiting, and nausea. Ultrasound (US) revealed hydronephrosis and ureter dilatation above the stone. All of these children had grade-3 hydronephrosis based on the Onen grading system during admission to the hospital. The lack of renal function on the DMSA scan was observed with an average of 22%. JJ-stent was inserted as a first-line treatment. A retrograde pyelogram revealed ureteral stricture at a length from 1 to 1.7 cm in the place where the stone was ingrown. Olbert's balloon dilatation under fluoroscopy was performed successfully in all children. We achieved an efficacy of 60% in our series. Renal function increased to an average of 36% on DMSA 3 months after surgery. The level of creatinine is shaped at an average of 0.6. On US, two children had no hydronephrosis while one child had grade-1 hydronephrosis. The longest follow-up is now 4 years, with the same good results. In conclusion, Olbert's balloon dilatation is an effective, safe, and minimally invasive tool for ureteral stricture in the hands of the endourological experienced pediatric urologist. But more prospective, randomized trials are still needed.